2010
DOI: 10.1039/c0cp00137f
|View full text |Cite
|
Sign up to set email alerts
|

Properties of non-IPR fullerene films versus size of the building blocks

Abstract: This perspective focuses on the cage size dependent properties of novel solid fullerene nanofilms grown by soft-landing of mass-selected C(n)(+) (48, 50, 52, 54, 56, 58, 62, 64, 66 and 68) onto room temperature graphite surfaces under ultra-high vacuum conditions. Such non-isolated-pentagon-ring (non-IPR) fullerene materials are not accessible to standard fullerene preparation methods. The component molecular building blocks of non-IPR films were generated by electron impact induced ionization/fragmentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 60 publications
7
38
0
Order By: Relevance
“…In particular, the approach seems to be attractive for the isomer specific synthesis of highly reactive non-IPR fullerenes. [22] Additionally, the technique allows simple post-synthetic manipulation of the nanostructures obtained, which is often a difficult task. The desired nanostructure can be synthesized, "purified" during ion selection and deposited on a surface.…”
Section: à2mentioning
confidence: 99%
“…In particular, the approach seems to be attractive for the isomer specific synthesis of highly reactive non-IPR fullerenes. [22] Additionally, the technique allows simple post-synthetic manipulation of the nanostructures obtained, which is often a difficult task. The desired nanostructure can be synthesized, "purified" during ion selection and deposited on a surface.…”
Section: à2mentioning
confidence: 99%
“…Soft‐ and reactive landing of mass‐selected ions onto surfaces has become a subject of substantial interest due to its potential as a method for the highly‐controlled preparation of materials for a variety of practical applications and fundamental investigations in chemistry, physics, and materials science (Grill et al, ; Gologan et al, , ; Laskin et al, ; Wang et al, ; Johnson et al, ; Cyriac et al, ; Verbeck et al, ). Recent studies have suggested future applications of ion soft landing in the separation of proteins and conformational enrichment of peptides (Gologan et al, ; Wang & Laskin, ), production of peptide and protein microarrays for high‐throughput biological screening (Ouyang et al, ; Blake et al, 2004b; Volny et al, ), preparation of thin films for use in composite materials (Saf et al, ; Rauschenbach et al, ), characterization of redox‐active proteins (Pepi et al, ), chiral enrichment of organic compounds (Nanita et al, ), processing of graphene (Rader et al, ), deposition of carbon clusters (Loffler et al, ), and preparation of model catalysts through deposition of ionic clusters, nanoparticles, and organometallics (Judai et al, ; Vajda et al, ; Kaden et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the D 5 h ‐C 70 cage, which dominates (besides I h ‐C 60 ) in conventional fullerene synthesis, might be regarded as a potential precursor for C 68 , especially when the close structural relationship is taken into account 10. The C 2 fragmentation of C 70 was predicted theoretically36 and recently such a process has been realized experimentally for bulk amounts 37. Due to the high symmetry of D 5 h ‐C 70 there are only eight nonequivalent possibilities for C 2 elimination.…”
Section: Resultsmentioning
confidence: 99%